Economics in America : an immigrant economist explores the land of inequality - Deaton, Angus (Princeton University Press, 2023)
"In 1995, the editor of the newsletter for the Royal Economic Society, who was a fan of Alistair Cooke's Letter from America on BBC Radio 4, suggested to Angus Deaton that he write a Letter about economic events in America. Twenty-five years later, Deaton, now a Nobel laureate and one of the world's most respected economists, submitted his fiftieth and final Letter from America. Over the years Deaton wrote about many topics, from the War on Terror to healthcare to becoming a US citizen, all from the perspective of a Scottish/British economist. In the letters he writes about both the economics profession in America as well as American society more generally. The letters show how he admired many aspects of American life while watching others with "fascinated horror." He wrote about the positive and negative aspects of American economics, including aspects that fostered and stifled new ideas. About American society, he "frequently wrote about aspects of American inequality, not only in income and wealth, but inequality across race and citizenship, and my evolving understanding that the American government, unlike the British government, which my parents and I had confidently looked to for protection, was frequently an oppressor, more often redistributing up than down.""--